The effect of restrictive measures on cross-border investment in the European Union - Wildmer Daniel Gregori; Michela Nardo (Publications Office of the European Union, 2020)
This study sheds light on the effect of restrictive policies, such as screening mechanisms, on mergers and acquisitions (M&A) flows into EU Member States in the period 2011-2018, by implementing an augmented gravity model. The results show that different restrictive measures affect cross-border investments unequally, and that the presence of screening mechanisms per se does not negatively affect cross-border investments. When we perform the analysis by sector, results suggest that cross-border investments in manufacturing and non-financial services are negatively by restrictive measures, such as restrictions on foreign personnel being employed in key positions, or restriction on the establishment of branches, land acquisition or profit and capital repatriations.
Keywords: F15; F21; G34; K20; 330; cross-border investment; M&A; EU; FDI; statutory restrictions; gravity model